Motor Condition Monitoring Using Wireless Sensors - Ahmad Syahir bin Sufian, Ahmad Syahir (2010)
The main aim of the project is to develop a wireless system that can be integrated with an existing wired system to monitor several variables/conditions of an electric motor. The objective was to build a prototype wireless motor condition monitoring with the usage of Zigbee modules.